The Effects of Secondhand Smoke Exposure on Infant Growth: a Prospective Cohort Study - Azam Baheiraei; Azar Shamsi; Afshin Mohsenifar; Anoshirvan Kazemnejad; Zinat Hatmi; Mohammad Milani; Ali Keshavarz (Acta Medica Iranica, 2015)
Mother's and infant exposure to cigarette smoke is one of the most important public health problems. There is no study in Iran evaluating the impact of cigarette smoke on infant growth and development. The purpose of this study was to determine the effects of cigarette. This prospective cohort study was conducted on 51 cigarette smoke-exposed infants (exposed group) and 51 non-exposed infants (non-exposed group). They were evaluated for weight, height and head circumference three times; five to seven days, two months and four months after birth. Urine samples were also collected in each turn. Exposure to secondhand smoke was assessed through questionnaires and urinary cotinine levels. The analysis was performed using an independent t-test, Mann-Whitney U test, chi-square and Fisher's exact and Kappa tests. Mean urinary cotinine level in the exposed group was 38.57±2.85 ng/mg creatinine at baseline, 86.95±1.16 at two months and 63.32±2.08 at four months of age. These indicated a gradual reduction of exposure from two to four months. The weight and height of the exposed group were significantly lower than the non-exposed group (P< 0.001) at two and four months after birth. The results of the present study showed that the exposure to secondhand smoke during infancy may lead to weight and height growth reduction in the first four months of life.